Boron-modified Kevlar aerogel flame retardant thermal insulation material and preparation method thereof
By introducing boron source and inorganic flame retardant components into Kevla aerogel, boron-modified Kevla aerogel was prepared by solvent thermal method, which solved the problem of insufficient flame retardant performance of existing materials, achieved the improvement of efficient flame retardant and thermal insulation performance, while maintaining low thermal conductivity.
Patent Information
- Application Number
- CN202510005031.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The flame retardant properties of existing Kevla aerogel insulation materials need to be further improved while maintaining low thermal conductivity.
By introducing boron source and inorganic flame retardant components, boron modified Kevla aerogel is prepared by solvent thermal method to ensure low thermal conductivity while improving flame retardant performance.
Boron-modified Kevla aerogel flame-retardant insulating material with three-dimensional nanoporous network structure, low density, low thermal conductivity and excellent flame retardant properties were obtained. The density was 0.083 g cm-3 to 0.369 g cm-3, the thermal conductivity was 0.0202 W m-1K-1 to 0.0359 W m-1K-1, the limit oxygen index (LOI) was 28.9% to 41.2%, and the carbon residue was 42.2% to 60.9%.
Smart Images

Figure CN119410023B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-efficiency heat-insulating flame-retardant materials, and specifically relates to a boron-modified Kevlar aerogel flame-retardant heat-insulating material and a preparation method thereof. Background Art
[0002] Kevlar fiber is an organic fiber with excellent comprehensive performance. This is not only due to its high strength and high modulus tensile properties, but also its high temperature resistance, flame retardancy, insulation and corrosion resistance. The original name of the material was poly (p-phenylene terephthalamide). The basic unit of the chemical structure is -[-CO-C6H4-CONH-C6H4-NH-]-. The amide group structure is connected to the benzene ring in the para position, so it is also called aramid 1414. Its structure is a planar rigid straight chain, and the molecules are crystallized in a network cross-linked manner to form a polymer. It has a simple preparation process, low cost, and excellent comprehensive performance. It is a high-performance fiber material that has been widely studied and applied.
[0003] In recent years, due to the excellent comprehensive properties of Kevlar fiber, its aerogel material has also received widespread attention.
[0004] Chinese patent application publication number CN116284973A discloses a boron nitride / aramid nanofiber aerogel and its preparation, and introduces a preparation method of aramid nanofiber aerogel based on Kevlar structure and its thermal insulation performance, and obtains a multifunctional integrated aerogel boron nitride / aramid nanofiber aerogel with thermal insulation, elasticity, flexibility, flame retardancy and thermal stability. However, in the preparation steps of the patent, the sol-gel stage adopts the method of adding a coagulation bath to the nanodispersion and stirring to prepare the hydrogel, and after the hydrogel is formed, it is shaped by suction filtration, resulting in a low porosity of the prepared composite aerogel, a cumbersome preparation process and a relatively high thermal conductivity (0.030-0.047 W m -1 K -1 ).
[0005] Chinese patent application publication number CN109608686A Kevlar aerogel film, its preparation method and application, introduces a preparation process and application of a Kevlar aerogel film, wherein the density, porosity and thermal conductivity properties are measured, and the density is 0.01-0.10 g cm -3 , porosity is 80-99.8%, thermal conductivity is 0.02-0.06 W m -1 K -1 Although it has good thermal insulation effect, the patent does not report the flame retardant properties of Kevlar aerogel.
[0006] A Kevlar / hexagonal boron nitride (h-BN) aerogel composite material has also been reported (H. Long, Y. Hu, J. Liu, et al. Robust and Density Tunable Kevlar / Hexagonal Boron Nitride Microribbon Aerogels with Excellent Thermal, Mechanical, and Oil-Absorption Properties, ACS Applied Materials & Interfaces, 16 (2024) 51421-51432). The thermal conductivity of this material is 0.0269~0.0450 W m -1 K -1 , the thermal stability is as high as 566℃, and it has good thermal insulation performance, but the document also does not specifically mention the flame retardant properties of the material.
[0007] Therefore, how to ensure the low thermal conductivity of Kevlar aerogel while further improving its residual carbon rate and flame retardant and heat-insulating properties to obtain Kevlar aerogel with high-efficiency flame retardant and heat-insulating properties is a technical problem that technicians in this field focus on. Summary of the invention
[0008] In view of the problem that the flame retardant properties of Kevlar aerogel thermal insulation materials in the prior art need to be further improved, the present invention provides a boron-modified Kevlar aerogel flame retardant thermal insulation material and a preparation method thereof. By introducing a boron source and adding an inorganic flame retardant component, the flame retardant properties are improved while ensuring low thermal conductivity, thereby obtaining a boron-modified Kevlar aerogel flame retardant thermal insulation material.
[0009] The technical solution of the present invention is as follows:
[0010] The invention adopts a solvent thermal method, takes a Kevlar nanofiber product as an initial raw material, stirs and disperses it in an alkaline solution to form a Kevlar nanofiber dispersion; then adds a boron compound to modify it, obtains a boron-modified Kevlar nanofiber solution, pours it into a high-pressure reactor and heats it together, obtains a boron-modified Kevlar initial gel under high temperature and high pressure conditions in the reactor, and then obtains a boron-modified Kevlar aerogel flame retardant and heat-insulating material through aging, solvent replacement and drying at room temperature and pressure.
[0011] The purpose of the present invention is achieved through the following technical solutions:
[0012] A method for preparing a boron-modified Kevlar aerogel flame retardant and heat-insulating material comprises the following steps:
[0013] (1) adding Kevlar nanofibers to an alkaline solution, wherein the mass ratio of Kevlar nanofibers to the alkaline solution is 1:(2-10), stirring at 10°C to 35°C for 30 minutes, so that the Kevlar nanofibers in the solution system are uniformly dispersed in the alkaline solution, and obtaining a dispersion of Kevlar nanofibers and the alkaline solution;
[0014] The alkali in the alkaline solution is selected from one of potassium hydroxide, sodium hydroxide, sodium tert-butoxide, potassium tert-butoxide, potassium hexamethyldisilazide, sodium hexamethyldisilazide, potassium ethoxide, triethylamine, tetramethylethylenediamine, sodium hydride, and potassium hydride;
[0015] The solvent in the alkaline solution is selected from one of hexamethylphosphoramide, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or acetonitrile and water solvent, wherein the water solvent accounts for 50%;
[0016] The mass concentration of the alkaline solution is 3wt%-8wt%;
[0017] (2) adding a boron compound to the dispersion of Kevlar nanofibers and alkaline solution obtained in step (1), wherein the mass ratio of the dispersion of Kevlar nanofibers and alkali to the boron compound is (2.5-10.5):1, and stirring at a constant speed at 10° C. to 35° C. until the mixture is uniformly mixed to obtain a boron-containing Kevlar nanofiber dispersion;
[0018] The boron compound is one of boric acid, phenylboric acid, diphenylboric acid and phenylboric anhydride;
[0019] (3) pouring the boron-containing Kevlar nanofiber dispersion obtained in step (2) into a high-pressure reactor, placing the high-pressure reactor in an oven and heating it to 100° C. to 160° C., and maintaining the constant temperature for 24 h to 96 h to obtain a boron-modified Kevlar fiber initial gel;
[0020] (4) aging the initial boron-modified Kevlar fiber gel obtained in step (3) at an aging temperature of 50° C. to 80° C. for 10 h to 40 h, and then cooling the gel at room temperature to obtain an aged boron-modified Kevlar fiber gel;
[0021] (5) soaking the aged boron-modified Kevlar fiber gel obtained in step (4) in a solvent, performing solvent replacement at 10° C. to 35° C., wherein the solvent is n-heptane or n-hexane, the number of solvent replacements is 3 to 5 times, and the soaking time for each time is 6 h to 10 h, to obtain a boron-modified Kevlar fiber final gel;
[0022] (6) The boron-modified Kevlar fiber final gel obtained in step (5) is placed in a room for drying at room temperature and pressure to obtain a boron-modified Kevlar aerogel flame retardant thermal insulation material. The boron-modified Kevlar aerogel flame retardant thermal insulation material has a three-dimensional nanoporous network structure and has the characteristics of low density and low thermal conductivity. The density is 0.083 g cm -3 ~0.369 gcm -3 , thermal conductivity is 0.0202 W m -1 K -1 ~0.0359 W m -1 K -1 , the limiting oxygen index (LOI) is 28.9%~41.2%, and the residual carbon rate is 42.2%~60.9%.
[0023] Furthermore, the mass ratio of the Kevlar fiber to the alkaline solution in step (1) is 1:6; the mass concentration of the alkaline solution is 3 wt %, wherein the alkali is sodium hydroxide and the solvent is hexamethylphosphoramide.
[0024] Furthermore, the mass ratio of the dispersion of Kevlar nanofibers and alkali to the boron compound in step (2) is 6.5:1.
[0025] Furthermore, in step (3), the high pressure reactor is placed in an oven and heated to 140° C., and the constant temperature is maintained for 48 hours.
[0026] Furthermore, the aging process described in step (4) is performed at an aging temperature of 65° C. and an aging time of 24 h.
[0027] Furthermore, in the solvent replacement described in step (4), the solvent is n-heptane, the number of solvent replacements is 4 times, and the soaking time for each time is 8 hours.
[0028] Furthermore, the drying in step (5) is carried out at room temperature and pressure, wherein the room temperature is 10° C. to 35° C. and the room pressure is one standard atmospheric pressure.
[0029] The present invention also relates to a boron-modified Kevlar aerogel flame-retardant thermal insulation material, which is obtained by the preparation method of the boron-modified Kevlar aerogel flame-retardant thermal insulation material. The boron-modified Kevlar aerogel flame-retardant thermal insulation material has a three-dimensional nanoporous network structure, and has the characteristics of low density, low thermal conductivity, etc. The density is 0.083 g cm -3 ~0.369 g cm -3 , thermal conductivity is 0.0202 W m -1 K - ~0.0359 W m -1 K -1, the limiting oxygen index (LOI) is 28.9%~41.2%, and the residual carbon rate is 42.2%~60.9%.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] 1. The method for preparing a boron-modified Kevlar aerogel flame-retardant and heat-insulating material described in the present invention adopts a solvent thermal method to prepare a boron-modified Kevlar initial gel. The solvent thermal method is a fully closed reaction system, and the reaction temperature is relatively low (100°C to 160°C). Therefore, the boron-modified Kevlar sol-gel process is simple, the reaction conditions are mild, there is no environmental pollution during the reaction process, and it is easy to realize industrial production.
[0032] 2. The boron-modified Kevlar aerogel flame-retardant thermal insulation material prepared by the preparation method of the present invention has a three-dimensional nanoporous network structure and has the characteristics of low density and low thermal conductivity. The density of the boron-modified Kevlar aerogel flame-retardant thermal insulation material prepared by the method of the present invention is 0.083 g cm -3 ~0.369 g cm -3 , thermal conductivity is 0.0202 W m -1 K -1 ~0.0359 W m -1 K -1 , the limiting oxygen index (LOI) is 28.9%~41.2%, and the residual carbon rate is 42.2%~60.9%. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The present invention discloses a general flow chart of a method for preparing a boron-modified Kevlar aerogel flame-retardant and heat-insulating material. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below by way of examples, but these examples should not be considered as limiting the present invention.
[0035] Embodiment 1:
[0036] A method for preparing a boron-modified Kevlar aerogel flame retardant thermal insulation material, such as Figure 1 As shown, the following steps are included:
[0037] (1) adding Kevlar nanofibers to a hexamethylphosphoramide alkaline solution having a mass concentration of 3 wt % sodium hydroxide, stirring at room temperature to uniformly disperse the Kevlar nanofibers in the solution system in the alkaline solution, and obtaining a dispersion of the Kevlar nanofibers and the alkaline solution in a mass ratio of 1:2;
[0038] (2) adding a certain mass of boric acid to the Kevlar nanofiber solution prepared in step (1), wherein the mass ratio of the Kevlar nanofiber solution to the boric acid is 10.5:1, and stirring at a constant speed for 30 min at room temperature to obtain a boron-containing Kevlar fiber solution;
[0039] (3) pouring the boron-containing Kevlar fiber solution obtained in step (2) into a high-pressure reactor, placing the high-pressure reactor in an oven and heating it to 140° C., and maintaining the constant temperature for 48 h, to obtain a boron-modified Kevlar fiber initial gel;
[0040] (4) aging the initial boron-modified Kevlar fiber gel obtained in step (3), wherein the aging time is set to 24 h and the aging temperature is set to 70° C., and then the gel is cooled at room temperature to obtain an aged boron-modified Kevlar fiber gel;
[0041] (5) replacing the aged boron-modified Kevlar fiber gel obtained in step (4) with n-heptane at room temperature, replacing the solvent once every 8 hours, for a total of 4 times, to obtain a boron-modified Kevlar fiber final gel;
[0042] (6) placing the boron-modified Kevlar fiber final gel obtained in step (5) in a room for drying at room temperature and pressure to obtain a boron-modified Kevlar fiber aerogel flame retardant thermal insulation material;
[0043] The density of the boron-modified Kevlar fiber aerogel flame retardant thermal insulation material is 0.083 g cm -3 , thermal conductivity is 0.0202 W m -1 K -1 The residual carbon rate was 42.2% and the LOI value was 29.0.
[0044] Embodiment 2:
[0045] A method for preparing a boron-modified Kevlar aerogel flame retardant thermal insulation material, such as Figure 1 As shown, the following steps are included:
[0046] (1) adding Kevlar nanofibers to a hexamethylphosphoramide alkaline solution having a mass concentration of 4 wt % sodium hydroxide, so that the Kevlar nanofibers in the solution system are uniformly dispersed in the alkaline solution, and obtaining a dispersion of the Kevlar nanofibers and the alkaline solution in a mass ratio of 1:10;
[0047] (2) adding a certain mass of boric acid to the Kevlar nanofiber solution prepared in step (1), wherein the mass ratio of the Kevlar nanofiber solution to the boric acid is 2.5:1, and stirring at a constant speed for 30 min at room temperature to obtain a boron-containing Kevlar fiber solution;
[0048] (3) pouring the boron-containing Kevlar fiber solution obtained in step (2) into a high-pressure reactor, placing the high-pressure reactor in an oven and heating it to 120° C., and maintaining the constant temperature for 72 h, to obtain a boron-modified Kevlar fiber initial gel;
[0049] (4) aging the initial boron-modified Kevlar fiber gel obtained in step (3), wherein the aging time is set to 10 h and the aging temperature is set to 80° C., and then the gel is cooled at room temperature to obtain an aged boron-modified Kevlar fiber gel;
[0050] (5) replacing the aged boron-modified Kevlar fiber gel obtained in step (4) with n-heptane at room temperature, replacing the solvent once every 10 hours for a total of 3 times, to obtain a boron-modified Kevlar fiber final gel;
[0051] (6) placing the boron-modified Kevlar fiber final gel obtained in step (5) in a room for drying at room temperature and pressure to obtain a boron-modified Kevlar fiber aerogel flame retardant thermal insulation material;
[0052] The density of the boron-modified Kevlar fiber aerogel flame retardant thermal insulation material is 0.360 g cm -3 , thermal conductivity is 0.0356 W m -1 K -1 The residual carbon rate is 60.9% and the LOI value is 41.0.
[0053] Embodiment 3:
[0054] A method for preparing a boron-modified Kevlar aerogel flame retardant thermal insulation material, such as Figure 1 As shown, the following steps are included:
[0055] (1) adding Kevlar nanofibers to a hexamethylphosphoramide alkaline solution having a mass concentration of 5 wt % sodium hydroxide, so that the Kevlar nanofibers in the solution system are uniformly dispersed in the alkaline solution, and obtaining a dispersion of the Kevlar nanofibers and the alkaline solution in a mass ratio of 1:2;
[0056] (2) adding a certain mass of phenylboric acid to the Kevlar nanofiber solution prepared in step (1), wherein the mass ratio of the Kevlar nanofiber solution to the phenylboric acid is 10.5:1, and stirring at a constant speed for 30 minutes at room temperature to obtain a boron-containing Kevlar fiber solution;
[0057] (3) pouring the boron-containing Kevlar fiber solution obtained in step (2) into a high-pressure reactor, placing the high-pressure reactor in an oven and heating it to 100° C., and maintaining the constant temperature for 96 hours to obtain a boron-modified Kevlar fiber initial gel;
[0058] (4) aging the initial boron-modified Kevlar fiber gel obtained in step (3), wherein the aging time is set to 32 h and the aging temperature is set to 60° C., and then the gel is cooled at room temperature to obtain an aged boron-modified Kevlar fiber gel;
[0059] (5) replacing the aged boron-modified Kevlar fiber gel obtained in step (4) with n-heptane at room temperature, replacing the solvent once every 6 hours for a total of 5 times, to obtain a boron-modified Kevlar fiber final gel;
[0060] (6) placing the boron-modified Kevlar fiber final gel obtained in step (5) in a room for drying at room temperature and pressure to obtain a boron-modified Kevlar fiber aerogel flame retardant thermal insulation material;
[0061] The density of the boron-modified Kevlar fiber aerogel flame retardant thermal insulation material is 0.088 g cm -3 , thermal conductivity is 0.020 9W m -1 K -1 The residual carbon rate is 42.2% and the LOI value is 28.9.
[0062] Embodiment 4:
[0063] A method for preparing a boron-modified Kevlar aerogel flame retardant thermal insulation material, such as Figure 1 As shown, the following steps are included:
[0064] (1) adding Kevlar nanofibers to a hexamethylphosphoramide alkaline solution having a mass concentration of 6 wt % sodium hydroxide, so that the Kevlar nanofibers in the solution system are uniformly dispersed in the alkaline solution, and obtaining a dispersion of the Kevlar nanofibers and the alkaline solution in a mass ratio of 1:10;
[0065] (2) adding a certain mass of phenylboric acid to the Kevlar nanofiber solution prepared in step (1), wherein the mass ratio of the Kevlar nanofiber solution to the phenylboric acid is 2.5:1, and stirring at a constant speed for 30 min at room temperature to obtain a boron-containing Kevlar fiber solution;
[0066] (3) pouring the boron-containing Kevlar fiber solution obtained in step (2) into a high-pressure reactor, placing the high-pressure reactor in an oven and heating it to 160° C., and maintaining the constant temperature for 24 h to obtain a boron-modified Kevlar fiber initial gel;
[0067] (4) aging the initial boron-modified Kevlar fiber gel obtained in step (3), wherein the aging time is set to 40 h and the aging temperature is set to 50° C., and then the gel is cooled at room temperature to obtain an aged boron-modified Kevlar fiber gel;
[0068] (5) replacing the aged boron-modified Kevlar fiber gel obtained in step (4) with n-heptane at room temperature, replacing the solvent once every 8 hours for a total of 4 times, to obtain a boron-modified Kevlar fiber final gel;
[0069] (6) placing the boron-modified Kevlar fiber final gel obtained in step (5) in a room for drying at room temperature and pressure to obtain a boron-modified Kevlar fiber aerogel flame retardant thermal insulation material;
[0070] The density of the boron-modified Kevlar fiber aerogel flame retardant thermal insulation material is 0.369 g cm -3 , thermal conductivity is 0.0354W m -1 K -1 The residual carbon rate is 60.6% and the LOI value is 40.9.
[0071] Embodiment 5:
[0072] A method for preparing a boron-modified Kevlar aerogel flame retardant thermal insulation material, such as Figure 1 As shown, the following steps are included:
[0073] (1) adding Kevlar nanofibers to a hexamethylphosphoramide alkaline solution having a mass concentration of 7 wt % sodium hydroxide, so that the Kevlar nanofibers in the solution system are uniformly dispersed in the alkaline solution, and obtaining a dispersion of the Kevlar nanofibers and the alkaline solution in a mass ratio of 1:2;
[0074] (2) adding a certain mass of phenylboric anhydride to the Kevlar nanofiber solution prepared in step (1), wherein the mass ratio of the Kevlar nanofiber solution to the phenylboric anhydride is 10.5:1, and stirring at a constant speed for 30 min at room temperature to obtain a boron-containing Kevlar fiber solution;
[0075] (3) pouring the boron-containing Kevlar fiber solution obtained in step (2) into a high-pressure reactor, placing the high-pressure reactor in an oven and heating it to 140° C., and maintaining the constant temperature for 4 to 8 hours to obtain a boron-modified Kevlar fiber initial gel;
[0076] (4) aging the initial boron-modified Kevlar fiber gel obtained in step (3), wherein the aging time is set to 10 h and the aging temperature is set to 80° C., and then the gel is cooled at room temperature to obtain an aged boron-modified Kevlar fiber gel;
[0077] (5) replacing the aged boron-modified Kevlar fiber gel obtained in step (4) with n-heptane at room temperature, replacing the solvent once every 10 hours for a total of 3 times, to obtain a boron-modified Kevlar fiber final gel;
[0078] (6) placing the boron-modified Kevlar fiber final gel obtained in step (5) in a room for drying at room temperature and pressure to obtain a boron-modified Kevlar fiber aerogel flame retardant thermal insulation material;
[0079] The density of the boron-modified Kevlar fiber aerogel flame retardant thermal insulation material is 0.089 g cm -3 , thermal conductivity is 0.0209 W m -1 K -1 The residual carbon rate is 42.6% and the LOI value is 29.1.
[0080] Embodiment 6:
[0081] A method for preparing a boron-modified Kevlar aerogel flame retardant thermal insulation material, such as Figure 1 As shown, the following steps are included:
[0082] (1) adding Kevlar nanofibers to a hexamethylphosphoramide alkaline solution having a mass concentration of 8 wt % sodium hydroxide, so that the Kevlar nanofibers in the solution system are uniformly dispersed in the alkaline solution, and obtaining a dispersion of the Kevlar nanofibers and the alkaline solution with a mass ratio of 1:10;
[0083] (2) adding a certain mass of phenylboric anhydride to the Kevlar nanofiber solution prepared in step (1), wherein the mass ratio of the Kevlar nanofiber solution to the phenylboric anhydride is 2.5:1, and stirring at a constant speed for 30 minutes at room temperature to obtain a boron-containing Kevlar fiber solution;
[0084] (3) pouring the boron-containing Kevlar fiber solution obtained in step (2) into a high-pressure reactor, placing the high-pressure reactor in an oven and heating it to 120° C., and maintaining the constant temperature for 72 h, to obtain a boron-modified Kevlar fiber initial gel;
[0085] (4) aging the initial boron-modified Kevlar fiber gel obtained in step (3), wherein the aging time is set to 32 h and the aging temperature is set to 60° C., and then the gel is cooled at room temperature to obtain an aged boron-modified Kevlar fiber gel;
[0086] (5) replacing the aged boron-modified Kevlar fiber gel obtained in step (4) with n-heptane at room temperature, replacing the solvent once every 10 hours for a total of 3 times, to obtain a boron-modified Kevlar fiber final gel;
[0087] (6) placing the boron-modified Kevlar fiber final gel obtained in step (5) in a room for drying at room temperature and pressure to obtain a boron-modified Kevlar fiber aerogel flame retardant thermal insulation material;
[0088] The density of the boron-modified Kevlar fiber aerogel flame retardant thermal insulation material is 0.361 g cm -3, thermal conductivity is 0.0358 W m -1 K -1 The residual carbon rate is 60.7% and the LOI value is 41.2.
[0089] Embodiment 7:
[0090] A method for preparing a boron-modified Kevlar aerogel flame retardant thermal insulation material, such as Figure 1 As shown, the following steps are included:
[0091] (1) adding Kevlar nanofibers to a hexamethylphosphoramide alkaline solution having a mass concentration of 5 wt % sodium hydroxide, so that the Kevlar nanofibers in the solution system are uniformly dispersed in the alkaline solution, and obtaining a dispersion of the Kevlar nanofibers and the alkaline solution in a mass ratio of 1:2;
[0092] (2) adding a certain mass of diphenylboric acid to the Kevlar nanofiber solution prepared in step (1), wherein the mass ratio of the Kevlar nanofiber solution to the diphenylboric acid is 10.5:1, and stirring at a constant speed for 30 min at room temperature to obtain a boron-containing Kevlar fiber solution;
[0093] (3) pouring the boron-containing Kevlar fiber solution obtained in step (2) into a high-pressure reactor, placing the high-pressure reactor in an oven and heating it to 140° C., and maintaining the constant temperature for 48 h, to obtain a boron-modified Kevlar fiber initial gel;
[0094] (4) aging the initial boron-modified Kevlar fiber gel obtained in step (3), wherein the aging time is set to 32 h and the aging temperature is set to 60° C., and then the gel is cooled at room temperature to obtain an aged boron-modified Kevlar fiber gel;
[0095] (5) replacing the aged boron-modified Kevlar fiber gel obtained in step (4) with n-heptane at room temperature, replacing the solvent once every 8 hours for a total of 4 times, to obtain a boron-modified Kevlar fiber final gel;
[0096] (6) placing the boron-modified Kevlar fiber final gel obtained in step (5) in a room for drying at room temperature and pressure to obtain a boron-modified Kevlar fiber aerogel flame retardant thermal insulation material;
[0097] The density of the boron-modified Kevlar fiber aerogel flame retardant thermal insulation material is 0.083 g cm -3 , thermal conductivity is 0.0206 W m -1 K -1 The residual carbon rate is 42.8% and the LOI value is 29.2.
[0098] Embodiment 8:
[0099] A method for preparing a boron-modified Kevlar aerogel flame retardant thermal insulation material, such as Figure 1 As shown, the following steps are included:
[0100] (1) adding Kevlar nanofibers to a hexamethylphosphoramide alkaline solution having a mass concentration of 5 wt % sodium hydroxide, so that the Kevlar nanofibers in the solution system are uniformly dispersed in the alkaline solution, and obtaining a dispersion of the Kevlar nanofibers and the alkaline solution in a mass ratio of 1:10;
[0101] (2) adding a certain mass of diphenylboric acid to the Kevlar nanofiber solution prepared in step (1), wherein the mass ratio of the Kevlar nanofiber solution to the diphenylboric acid is 2.5:1, and stirring at a constant speed for 30 min at room temperature to obtain a boron-containing Kevlar fiber solution;
[0102] (3) pouring the boron-containing Kevlar fiber solution obtained in step (2) into a high-pressure reactor, placing the high-pressure reactor in an oven and heating it to 140° C., and maintaining the constant temperature for 48 h, to obtain a boron-modified Kevlar fiber initial gel;
[0103] (4) aging the initial boron-modified Kevlar fiber gel obtained in step (3), wherein the aging time is set to 32 h and the aging temperature is set to 60° C., and then the gel is cooled at room temperature to obtain an aged boron-modified Kevlar fiber gel;
[0104] (5) replacing the aged boron-modified Kevlar fiber gel obtained in step (4) with n-heptane at room temperature, replacing the solvent once every 8 hours for a total of 4 times, to obtain a boron-modified Kevlar fiber final gel;
[0105] (6) placing the boron-modified Kevlar fiber final gel obtained in step (5) in a room for drying at room temperature and pressure to obtain a boron-modified Kevlar fiber aerogel flame retardant thermal insulation material;
[0106] The density of the boron-modified Kevlar fiber aerogel flame retardant thermal insulation material is 0.365 g cm -3 , thermal conductivity is 0.0359 W m -1 K -1 The residual carbon rate is 60.9% and the LOI value is 41.2.
[0107] In the above process of preparing boron-modified Kevlar aerogel flame retardant thermal insulation material:
[0108] The alkaline solvent is added in step (1) to dissolve the Kevlar fiber monomer and obtain a Kevlar fiber dispersion of a certain concentration. The alkaline substance and the type of solvent have little effect on the material properties.
[0109] The type of boron compound added in step (2) and the mass ratio of Kevlar fiber dispersion to boron compound have a significant effect on the performance of the material;
[0110] In step (3), as long as the reaction temperature is kept within the range of 100-160 °C, a stable gel can be obtained and the effect on the performance of the material can be ignored;
[0111] Step (4) aging to make the structure of the initial gel of boron-modified Kevlar fiber more stable;
[0112] The purpose of step (5) solvent replacement is to replace the organic solvent in the gel and reduce the capillary tension in the subsequent drying process;
[0113] Step (6) drying at room temperature and pressure is to remove the solvent from the gel, and finally prepare the boron-modified Kevlar aerogel flame retardant thermal insulation material.
[0114] During the preparation process, as long as the influencing factors such as aging temperature and time, replacement times, etc. are within the above range, the influence on the density, thermal conductivity, residual carbon rate and limiting oxygen index of the boron-modified Kevlar aerogel flame retardant thermal insulation material can be basically ignored. The performance of the boron-modified Kevlar aerogel flame retardant thermal insulation material is mainly affected by the mass ratio of Kevlar nanofibers to alkaline solution, the type of boron compound, and the mass ratio of Kevlar fiber dispersion to boron compound. The greater the mass ratio of Kevlar to alkaline solution, the greater the density of the material and the higher the thermal conductivity; the higher the content of boron compound added, the greater the density, the higher the thermal conductivity, the higher the limiting oxygen index, and the higher the residual carbon rate.
[0115] The specific preparation process parameters and performance parameters of boron-modified Kevlar aerogel flame retardant thermal insulation materials are shown in Tables 1 to 5.
[0116] Comparative Example 1:
[0117] The difference between Comparative Example 1 and Example 1 is that the preparation of the boron compound solution in step (2) is omitted, and the rest is the same as Example 1;
[0118] The density of the prepared Kevlar fiber aerogel flame retardant thermal insulation material is 0.099 g cm -3 , thermal conductivity is 0.0187Wm -1 K -1 , the residual carbon rate is 38.2%, and the LOI value is 26.1;
[0119] The results show that boron compounds are beneficial to improving thermal conductivity, carbon residue rate and limiting oxygen index (LOI), thereby improving the thermal insulation and flame retardant ability of Kevlar fiber aerogel.
[0120] Comparative Example 2:
[0121] The difference between Comparative Example 2 and Example 1 is that the mass ratio of the Kevlar fiber dispersion to the boron compound is 15:1, and the others are the same as Example 1;
[0122] The density of the boron-modified Kevlar fiber aerogel flame retardant thermal insulation material is 0.088 g cm -3 , thermal conductivity is 0.0191 W m -1 K -1 , the residual carbon rate is 39.0%, and the LOI value is 27.0;
[0123] The results show that a too low proportion of boron compounds will not improve the thermal conductivity, carbon residue rate and limiting oxygen index (LOI) enough to achieve the required thermal insulation and flame retardant indicators.
[0124] Comparative Example 3:
[0125] The difference between Comparative Example 3 and Example 1 is that the mass ratio of the Kevlar fiber dispersion to the boron compound is too low, 1:1, and the rest is the same as Example 1;
[0126] The boron-modified Kevlar fiber aerogel obtained could not stabilize the gel;
[0127] The results show that too high a proportion of boron compounds will result in poor gelation or even no gelation of the original Kevlar fiber dispersion.
[0128] Table 1: Preparation process parameters and performance parameters of boron-modified Kevlar aerogel flame retardant thermal insulation materials (the type of boron compound is boric acid)
[0129]
[0130] Table 2: Preparation process parameters and performance parameters of boron-modified Kevlar aerogel flame retardant thermal insulation materials (the type of boron compound is boric acid or phenylboric acid)
[0131]
[0132] Table 3: Preparation process parameters and performance parameters of boron-modified Kevlar aerogel flame retardant thermal insulation materials (the type of boron compound is phenylboric acid or phenylboric anhydride)
[0133]
[0134] Table 4: Preparation process parameters and performance parameters of boron-modified Kevlar aerogel flame retardant thermal insulation materials (boron compound type is phenylboric anhydride or diphenylboric acid)
[0135]
[0136] Table 5: Preparation process parameters and performance parameters of boron-modified Kevlar aerogel flame retardant thermal insulation materials (the type of boron compound is diphenylboric acid)
[0137]
[0138] The above are only preferred implementations of the present invention. The protection scope of the present invention is not limited to the above embodiments. Various process schemes that are not substantially different from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A method for preparing a boron-modified Kevlar aerogel flame retardant and heat-insulating material, characterized in that: The following steps are involved: (1) adding Kevlar nanofibers to an alkaline solution, wherein the mass ratio of Kevlar nanofibers to the alkaline solution is 1:(2-10), stirring at 10°C to 35°C for 30 minutes, so that the Kevlar nanofibers in the solution system are uniformly dispersed in the alkaline solution, and obtaining a dispersion of Kevlar nanofibers and the alkaline solution; The alkali in the alkaline solution is selected from one of potassium hydroxide, sodium hydroxide, sodium tert-butoxide, potassium tert-butoxide, potassium hexamethyldisilazide, sodium hexamethyldisilazide, potassium ethoxide, triethylamine, tetramethylethylenediamine, sodium hydride, and potassium hydride; The solvent in the alkaline solution is selected from one of hexamethylphosphoramide, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or acetonitrile and water solvent, wherein the water solvent accounts for 50%; The mass concentration of the alkaline solution is 3wt%-8wt%; (2) adding a boron compound to the dispersion of Kevlar nanofibers and alkaline solution obtained in step (1), wherein the mass ratio of the dispersion of Kevlar nanofibers and alkali to the boron compound is (2.5-10.5):1, and stirring at a constant speed at 10° C. to 35° C. until the mixture is uniformly mixed to obtain a boron-containing Kevlar nanofiber dispersion; The boron compound is one of boric acid, phenylboric acid, diphenylboric acid and phenylboric anhydride; (3) pouring the boron-containing Kevlar nanofiber dispersion obtained in step (2) into a high-pressure reactor, placing the high-pressure reactor in an oven and heating it to 100° C. to 160° C., and maintaining the constant temperature for 24 h to 96 h to obtain a boron-modified Kevlar fiber initial gel; (4) aging the initial boron-modified Kevlar fiber gel obtained in step (3) at an aging temperature of 50° C. to 80° C. for 10 h to 40 h, and then cooling the gel at room temperature to obtain an aged boron-modified Kevlar fiber gel; (5) soaking the aged boron-modified Kevlar fiber gel obtained in step (4) in a solvent, performing solvent replacement at 10° C. to 35° C., wherein the solvent is n-heptane or n-hexane, the number of solvent replacements is 3 to 5 times, and the soaking time for each time is 6 h to 10 h, to obtain a boron-modified Kevlar fiber final gel; (6) The boron-modified Kevlar fiber final gel obtained in step (5) is placed in a room for drying at room temperature and pressure to obtain a boron-modified Kevlar aerogel flame retardant thermal insulation material. The boron-modified Kevlar aerogel flame retardant thermal insulation material has a three-dimensional nanoporous network structure and has the characteristics of low density and low thermal conductivity. The density is 0.083 g cm -3 ~0.369 g cm -3 , thermal conductivity is 0.0202 W m -1 K -1 ~0.0359 W m -1 K -1 , the limiting oxygen index is 28.9%~41.2%, and the residual carbon rate is 42.2%~60.9%.
2. The method for preparing a boron-modified Kevlar aerogel flame retardant and heat-insulating material according to claim 1, characterized in that: The mass ratio of the Kevlar fiber to the alkaline solution in step (1) is 1:6; the mass concentration of the alkaline solution is 3wt%, wherein the alkali is sodium hydroxide and the solvent is hexamethylphosphoramide.
3. The method for preparing a boron-modified Kevlar aerogel flame retardant and heat-insulating material according to claim 1, characterized in that: The mass ratio of the Kevlar nanofibers and the dispersion of the alkali: the boron compound in step (2) is 6.5:
1.
4. The method for preparing a boron-modified Kevlar aerogel flame retardant and heat-insulating material according to claim 1, characterized in that: In step (3), the high pressure reactor is placed in an oven and heated to 140° C. and maintained at this constant temperature for 48 hours.
5. The method for preparing a boron-modified Kevlar aerogel flame retardant and heat-insulating material according to claim 1, characterized in that: The aging process described in step (4) is performed at a temperature of 65° C. and a time of 24 h.
6. The method for preparing a boron-modified Kevlar aerogel flame retardant and heat-insulating material according to claim 1, characterized in that: In the solvent replacement described in step (5), the solvent is n-heptane, the number of solvent replacements is 4 times, and the soaking time for each time is 8 hours.
7. The method for preparing a boron-modified Kevlar aerogel flame retardant and heat-insulating material according to claim 1, characterized in that: The drying in step (6) is carried out at room temperature and pressure, wherein the room temperature is 10°C to 35°C and the room pressure is one standard atmospheric pressure.
8. A boron-modified Kevlar aerogel flame retardant thermal insulation material, characterized in that: The boron-modified Kevlar aerogel flame-retardant thermal insulation material is prepared by the method for preparing the boron-modified Kevlar aerogel flame-retardant thermal insulation material according to any one of claims 1 to 7. The boron-modified Kevlar aerogel flame-retardant thermal insulation material has a three-dimensional nanoporous network structure and has the characteristics of low density and low thermal conductivity. The density is 0.083 g cm -3 ~0.369 g cm -3 , thermal conductivity is 0.0202 W m -1 K -1 ~0.0359 W m -1 K -1 , the limiting oxygen index is 28.9%~41.2%, and the residual carbon rate is 42.2%~60.9%.
Citation Information
Patent Citations
Kevlar aerogel film, and preparation method and application thereof
CN109608686A
Boron nitride / aramid nanofiber aerogel and preparation method thereof
CN116284973A
High-mechanical-strength aerogel thermal insulation material and preparation method thereof
CN119059832A